2018
DOI: 10.1136/bmjresp-2017-000256
|View full text |Cite
|
Sign up to set email alerts
|

Initiation, scale-up and outcomes of the Cambodian National MDR-TB programme 2006–2016: hospital and community-based treatment through an NGO–NTP partnership

Abstract: IntroductionProlonged inpatient multidrug-resistant tuberculosis (MDR-TB) treatment for all patients is not sustainable for high-burden settings, but there is limited information on community-based treatment programme outcomes for MDR-TB.MethodsThe Cambodian Health Committee, a non-governmental organisation (NGO), launched the Cambodian MDR-TB programme in 2006 in cooperation with the National Tuberculosis Program (NTP) including a community-based treatment option as a key programme component. The programme wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…38 Another study reported four XDR-TB cases (0.7%) and only one pre-XDR-TB case (0.1%) confirmed by DST among MDR-TB patients between 2006 and 2016, but only the patients who did not respond to the treatment regimen were tested for SLD resistance. 13 The present study reports the first description of SLD drug resistance in M.tb in Cambodia using a combination of molecular screening for mutations in the gyrA/B gene conferring FQ resistance and the rrs-F2 gene conferring SLID resistance followed by pDST confirmation. Overall, only 25 of the 37 M.tb isolates harboring mutations in the gyrA/B and/or rrs-F2 genes were resistant to FQ or SLID by pDST.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…38 Another study reported four XDR-TB cases (0.7%) and only one pre-XDR-TB case (0.1%) confirmed by DST among MDR-TB patients between 2006 and 2016, but only the patients who did not respond to the treatment regimen were tested for SLD resistance. 13 The present study reports the first description of SLD drug resistance in M.tb in Cambodia using a combination of molecular screening for mutations in the gyrA/B gene conferring FQ resistance and the rrs-F2 gene conferring SLID resistance followed by pDST confirmation. Overall, only 25 of the 37 M.tb isolates harboring mutations in the gyrA/B and/or rrs-F2 genes were resistant to FQ or SLID by pDST.…”
Section: Discussionmentioning
confidence: 85%
“…This retrospective cross-sectional study included FLDresistant M.tb isolates taken from the collection of clinical isolates obtained via a platform established for routine screening of MDR-TB among high-risk groups by the National Tuberculosis Program (NTP). 13 Since 2012, people at risk of developing MDR-TB were screened using Xpert MTB/RIF, followed by culture and phenotypic drug susceptibility testing (pDST) for FLD. All confirmed RIF resistant (RR) or MDR-TB cases received a 24-month standardized regimen in two phases: an 8-month intensive phase and a 16-month continuation phase.…”
Section: Mtb Strain Collection and Ntp Routine For Mdr-tb Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in China have shown that urban migrants have higher TB rates, more drug resistance, and poorer treatment outcomes than urban residents [32, 33]. Several decentralized models of care for MDR-TB have been introduced to improve the linkage between diagnosis and treatment initiation especially for patients from rural areas [34, 35]. MDR-TB patients treated under community-based care involving healthcare workers and treatment supporters at sub-district or village level achieved equally high treatment success as those with hospital-based initiation [36].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2009, treatment success and completion rates have declined steadily. Rising rates of drug-resistant TB also indicate that poor adherence may be a concern [ 30 ].…”
Section: Methodsmentioning
confidence: 99%